Curso y pronóstico del trastorno Autista - López Gómez , Santiago (2022)
Autistic disorder remains as a disorder of unknown aetiology , with heterogeneous manifestations related to three main diagnostic groups: alterations in social behaviours, alterations in language and communications, and behavioural patterns, interactions or activities that are restricted and stereotyped. Its course is chronic, but with its own characteristic evolutive and fluctuating special features that eventually change with development. A review of current researches that try to summarize its syntomatic dispersion, course and prognosis is made. Finally , it is also presented a descriptive view of the situation, at symptomatic level, of its main manifestations